Feeding convergence of Gadwall, Coot and other herbivorous waterfowl species wintering in the Camargue: a preliminary approach - Allouche, Laurent; Tamisier, Alain (Wildfowl, 1984)
New data on the food habits of Gadwall Anas strepera and Coot Fulica atra in the Camargue compared to the available information on Wigeon A. penelope, Pochard Aythya ferina and Red-crested Pochard Netta rufina allow a preliminary comprehensive description of the relation of the herbivorous waterfowl community towards its food supply. Gadwall, Coot and most Wigeon, the three most abundant herbivorous species, are mainly dependent on the vegetative parts of Potamae (P. pectinatus, P. pusillus, Zannichellia palustris and Ruppia sp.). Those marshes in which they feed are rich in beds of Ranunculus sp., Myriophyllum sp. and Characae, which are commonly eaten by the same species outside the Camargue. Pochard mainly feed on the tubers and seeds of P. pectinatus, whereas Red-crested Pochard, numerically the less important species, probably eat the vegetative parts of Characae and the seeds of Scirpus litoralis. There is thus an impressive convergence of herbivorous species on the same family and plants (Potamae) without giving rise to a strong interspecific competition. We suspect that the numerical size of this guild is low as compared to the carrying capacity of the Camargue.